Application of bagging and particle swarm optimisation techniques to predict technology sector stock prices in the era of the COVID-19 pandemic using the support vector regression method. (13th June 2023) - Sulastri, Heni; Intani, Sheila Maulida; Rianto, Rianto
The increase in positive cases of COVID-19 not only affects the health and lifestyle, but also the economy and the stock market. Tech and digital sector stocks can be predicted to be one of the most profitable. Therefore, the prediction of the stock price is required to be able to forecast the prospects of investment in the future. In this study, the prediction of the stock prices of Multipolar Technologies Ltd. (MLPT) was carried out using the support vector regression (SVR) method with bootstrap aggregation (bagging) technique and particle swarm optimisation (PSO) as SVR optimisation. From the results of the prediction process, it is shown that the application of bagging and PSO techniques in predicting stock prices in the technological sector can reduce the root mean squared error (RMSE) value on the SVR, the RMSE value from 22.142 to 21.833. Although it does not have a big impact, it is better to apply a combination of bagging and PSO techniques to SVR than one of them (SVR/SVR - PSO/SVR-Bagging).